Electrophysiological Changes in Depressive Patients with Non-Suicidal Self-Injury: An Event-Related Potential Study and Source Analysis - Sehoon Shim (BJPsych Open)
Aims: Non-suicidal self-injury (NSSI) has been increasingly observed among adolescents as a maladaptive coping mechanism to alleviate emotional distress. Despite its high prevalence, the neurobiological underpinnings linking interpersonal distress to cognitive control deficits remain underexplored. Electroencephalography (EEG) studies suggest that the no-go P3 component may serve as a biomarker for impulsivity and response inhibition, offering insights into the mechanisms underlying NSSI behaviours. This study aimed to investigate the relationship between psychological characteristics, neural activity, and cognitive control in adolescents with NSSI compared with healthy controls (HC).